2021
DOI: 10.3389/fvets.2021.673822
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Microbiota of Tibetan Sheep (Ovis aries) Adaptation to Extremely Cold Season on the Qinghai-Tibetan Plateau

Abstract: The Qinghai-Tibet Plateau is characterized by low temperatures and hypoxia, and this feature is more obvious in the winter. However, it is not clear how Tibetan sheep adapt to extreme cold climates. To address this, we used physiological methods combined with next-generation sequencing technology to explore the differences in growth performance, forage nutrient digestion, serum biochemical indexes, and rumen microbial communities of Tibetan sheep (Ovis aries) between the summer and winter. In the summer, owing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 59 publications
(89 reference statements)
3
18
1
Order By: Relevance
“…Fibrobacter, Treponema_2, Saccharofermentans and Ruminococcus_1 were higher in winter. Fan's et al ( 57 ) results showed that Ruminococcus_1 was more concentrated in summer, while our results showed that Ruminococcus_1 and Saccharofermentans were more concentrated in winter, which may be due to relatively stable source of nutrients. In addition, in the cold winter, more energy was needed to resist the cold.…”
Section: Discussioncontrasting
confidence: 57%
“…Fibrobacter, Treponema_2, Saccharofermentans and Ruminococcus_1 were higher in winter. Fan's et al ( 57 ) results showed that Ruminococcus_1 was more concentrated in summer, while our results showed that Ruminococcus_1 and Saccharofermentans were more concentrated in winter, which may be due to relatively stable source of nutrients. In addition, in the cold winter, more energy was needed to resist the cold.…”
Section: Discussioncontrasting
confidence: 57%
“…Rikenellaceae_RC9_gut_group , which is the main gene of Rikenellaceae, plays an important role in the fermentation of carbohydrates and crude protein ( 46 , 47 ). Fan et al ( 8 ) also revealed that Tibetan sheep could enhance forage degradation and fermentation by increasing the relative abundance of Bacteroidetes, Prevotella_1 , and Prevotellaceae_UCG-003 during the summer season compared with the winter season. Christensenellaceae are belonged to Firmicutes, which widespread in the intestines and mucous membranes of humans and animals and are important for host health due to several enzymes ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that Tibetan sheep suffered serious live-weight loss (−20.54%) under traditional pastoral herding, resulting in severe economic loss during the cold season ( 7 ). In addition to growth performance and economic benefits, cold season grazing also reduces growth hormone levels and damages the immune defense system of Tibetan sheep ( 8 ). Therefore, scientific management and rearing are particularly important in Tibetan sheep production.…”
Section: Introductionmentioning
confidence: 99%
“…They have been grazed and used by local herdsmen for meat, milk, and fuel (the dry feces) for several centuries (Cui et al, 2020 ). Modification of the intestinal microbiomes of these high-altitude ruminants in response to the unique ecological environment of the QTP has been extensively studied (Ma et al, 2019b ; Liu et al, 2020a , c , 2021 ; Fan et al, 2021 ). By way of illustration, S adapt to changes in the plant phenological period by altering their rumen microbial community structure and function (Liu et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%